TOPICAL ISSUES OF REGULATION AND CONTROL IN THE SPHERE OF INSURANCE - Nina F. Kuzovleva (Статистика и экономика, 2016)
The article deals with urgent problems of regulation in connection with the transfer of responsibility for supervision of the insurance industry to the Central Bank of the Russian Federation. It is proposed to tighten supervision sectors of the insurance market, engaged in long term insurance and obligatory types of insurance, as well as the structure of insurance reserves, transfered in trust management.